2021
DOI: 10.1093/ageing/afab231
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes duration and the risk of dementia: a cohort study based on German health claims data

Abstract: Objective Diabetes is a risk factor for dementia but little is known about the impact of diabetes duration on the risk of dementia. We investigated the effect of type 2 diabetes duration on the risk of dementia. Design Prospective cohort study using health claims data representative for the older German population. The data contain information about diagnoses and medical prescriptions from the in- and outpatient sector. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 44 publications
2
18
0
1
Order By: Relevance
“…Further, we found that T2DM patients requiring antidiabetic drugs had a longer duration of disease than Non-drug patients ( Supplementary Table 2 , P < 0.001). This may be related to the fact that these patients with advanced diabetes tend to have more severe brain abnormalities due to their continued deterioration of islet function ( Reinke et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we found that T2DM patients requiring antidiabetic drugs had a longer duration of disease than Non-drug patients ( Supplementary Table 2 , P < 0.001). This may be related to the fact that these patients with advanced diabetes tend to have more severe brain abnormalities due to their continued deterioration of islet function ( Reinke et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that SVC density in EOD patients significantly correlated with PWMH scores assessed with the Fazekas scale. Retinal imaging studies using fundus photography showed that changes in the retinal vein (located in the SVC) are associated with cardiovascular risk factors such as hypertension [ 44 , 45 ] and diabetes [ 46 , 47 ], which are linked with dementia. Besides, it has been hypothesized that enlargement of the retinal venules reflects endothelial dysfunction [ 48 ], which is a classical indicator of ischemia in the retina and hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the natures of administrative data or claims data, which are usually presumed for reimbursement rather than for research,5 6 scholars have proposed important issues that may pose threats and limitations to such studies, including the quality and reliability of the data,7 8 the lack of consensus and standardisation across the databases, and the doubt of data accuracy as a result of erroneous linkage 9 10. Furthermore, despite being powerful, studies based on HCD are still vulnerable to the under-recording of dementia, resulting in under-representativeness of the target group and threats to generalisability of the study results 11…”
Section: Introductionmentioning
confidence: 99%